Living Hadis of Tolerance in Multicultural Education: A Leadership Study in Pesantren Al Mukmin Ngruki Sukoharjo Surakarta - Abdul Matin bin Salman (Jurnal Pendidikan Islam, 2017)
Pesantren (Islamic Boarding School) Al-Mukmin Ngruki is underestimated by some of Indonesian people. It is considered as the center of radical teachings which has no tolerance to others. But in fact, the values of tolerance can be found in the teaching materials. With bayani and burhani approaches in understanding religious source, pesantren Al-Mukmin persists to implant the values of tolerance to the students in the learning process, such as behave positively toward differences and plurality. The leaders of pesantren make those values as the starting point to strengthen multicultural education in pesantren with role modeling, habituation, attention, and advices in living those values.